Pengaruh PDB, Inflasi, Kurs, CAR, BOPO, NPF, Dan BI Rate terhadap Pertumbuhan Bank Muamalat Indonesia Periode 2017 – 2022 - Abdulloh, Lukman; Diniati , Bintis Ti`anatud (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to examine the effect of GDP (Gross Domestic Product), Inflation, Exchange Rate, CAR (Capital Adequacy Ratio), BOPO (Operating Cost Operating Income), NPF (Non Performing Finance) and BI Rate on Bank Muamalat's growth in 2017-2022 as seen from the growth of its assets. The population of this study is the entire quarterly report data of PT Bank Muamalat Indonesia during the study period. This study used multiple linear regression method with the help of E-views 12 application. The results showed that the BI Rate, Inflation had a significant positive effect, while the Exchange Rate and NPF had a significant positive effect on the growth of PT. Bank Muamalat Indonesia. Other results show that BOPO, GDP and CAR variables have an insignificant effect on the growth of PT assets. Bank Muamalat Indonesia. Keywords: GDP; Inflation; Exchange Rate; CAR; BOPO;  NP; BI Rate; Asset Growth